Expression profiling of stress responsive genes in cell suspension of Elettaria cardamomum (L.) Maton under abiotic stress - Dharan, Soumya S.; Sabu, K. K. (Journal of Plantation Crops, 2023)
Cardamom is an economically important spice, valued for its multiple utility from culinary to medical purposes. The plant is highly susceptible to both abiotic and biotic stresses. Despite the fact that several studies focusing on stress in cardamom have been conducted; a molecular analysis at the cellular level has not been reported. This study highlights the molecular response of homogenous population of cardamom cell suspension following the temperature and drought stresses for a short period of time (20 mins). Temperature stress at 30, 35, and 40°C caused a significant increase in the transient expression of genes, sHSP 17.8 and sHSP 17.9, which are molecular chaperones involved in protein folding coping with the heat stress response of plants. Drought stress with various concentrations of PEG 6000 has demonstrated only a little increase in the expression of transcription factors, WRKY 35 and WRKY 71. The study implies that sHSP 17.8 and sHSP 17.9 play a crucial role during heat stress, which is a major limiting factor for the cultivation of cardamom in lower altitudes where atmospheric temperature is usually high. But WRKY 35 and WRKY 71 genes are found not to have a high impact at the cellular level in response to drought stress in cardamom when it is exposed to a brief duration of drought. Understanding the molecular mechanism underlying abiotic stress response in cardamom will aid in developing elite varieties adaptable to lower altitudes and to cope with the frequent climatic variations.